2002
DOI: 10.1518/0018720024494810
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Urgency of Speech Warnings: Semantics versus Acoustics

Abstract: The relationship between the semantics of words and the acoustics of the way they are spoken is explored. Actors spoke warning signal words in an urgent, nonurgent and monotone style, and participants rated the urgency of the words. Results showed effects for signal word and style of presentation. Acoustic analysis showed that the urgent words were spoken at higher frequency with a broader pitch range and were louder than the nonurgent or monotone words. These acoustic differences were used to synthesize artif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
81
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 22 publications
16
81
2
Order By: Relevance
“…Hellier et al [9] also found an influence of acoustics and speaking style in the ratings of urgency. Signal words spoken urgently created higher ratings compared to nonurgently, which in turn were higher compared to words spoken in a monotone manner.…”
Section: Designing Urgency In Speechmentioning
confidence: 92%
See 1 more Smart Citation
“…Hellier et al [9] also found an influence of acoustics and speaking style in the ratings of urgency. Signal words spoken urgently created higher ratings compared to nonurgently, which in turn were higher compared to words spoken in a monotone manner.…”
Section: Designing Urgency In Speechmentioning
confidence: 92%
“…before each L M and "Notice!" before each L L , since these words have shown to provide distinctively different urgency ratings in previous studies [2,9]. The resulting messages were "Danger!…”
Section: Warning Designmentioning
confidence: 97%
“…In terms of applicability, Edworthy and her colleagues (e.g. Edworthy, Loxley, & Dennis, 1991;Hellier, Edworthy, & Dennis, 1993;Hellier, Edworthy, Weedon, Walters, & Adams, 2002) have repeatedly shown that designing warning sounds based on the results of magnitude estimation studies leads to predictable orderings of 'urgency', and therefore to better auditory warning systems. Guillaume, Pellieux, Chastres and Drake (2003) have recently argued that, at least in the case of warnings, in addition to acoustic variables, such as frequency or repetition rate, more cognitive factors need to be considered.…”
mentioning
confidence: 99%
“…If a voice alarm is better than beeping, is a female voice better than a male voice? A female voice was chosen in the above studies because of research showing that a female voice was perceived as more urgent than a male voice by individuals when awake [37]. However, given that the low pitched T-3 was found to be as effective as the female voice [10] urgency may not be a critical factor in differential arousal from sleep.…”
Section: Implications and Conclusionmentioning
confidence: 99%